Correlates of smoking initiation among young adults in Ukraine: a cross-sectional study - Krasovsky Konstantin S; Andreeva Tatiana I; Semenova Daria S (BMC, 2007)
Abstract Background Aim: To estimate the impact of smoking restrictions in homes and schools, and tobacco advertising and information on smoking initiation by young people in Ukraine. Methods Data of 609 young people aged 15-29 was taken from the national representative survey conducted in June 2005. Outcome measures: The reported age of cigarette initiation was used to characterize the start of smoking experimentation, and the reported age of daily smoking initiation was considered to be a characteristic of established smoking. Analysis: survival analysis Cox proportional hazard regression models were used. Results Age of smoking initiation was reported by 87% of young men and 61% of young women, the beginning of daily smoking by 71% and 33% respectively. Being frequently exposed to second-hand smoke and having no household smoking restrictions was associated with a higher risk of earlier smoking initiation both for men and women. For women, this risk was associated with age, HR = 0.95, (95% CI 0.91-0.98), that is, younger girls were more likely to smoke their first cigarette earlier in their lifetime. Those women had a higher risk of early smoking initiation who reported to receive tobacco-related information from magazines, HR = 1.40 (1.01-1.92), and outdoor tobacco advertising, HR = 1.99 (1.45-2.75). With both men and women, the risk of establishing daily smoking was higher in those with lower levels of tobacco-related knowledge and less household smoking restrictions. For women, the risk was higher in those who live in larger cities HR = 1.77 (1.10-2.86), and who received information about tobacco smoking from colleagues or friends HR = 1.83 (1.13-2.95). Conclusion Encouraging people to eliminate their homes of tobacco smoke and tobacco advertising bans can be effective measures in preventing the initiation of smoking among young people. Young female smoking initiation is of special concern in Ukraine, since they are more responsive to tobacco marketing and pro-smoking peer influence.